Doha Development Agenda and the interests of CEE countries - Miškinis, Algirdas (Program rozwoju z Doha a interesy krajów Europy Środkowo-Wschodniej, 2011)
The future of world trade to a large extent depends on the success of trade negotiations at Doha round. Conflicting views on agriculture, medicine, and the treatment of developing countries make it difficult to match the interest of different countries. There is a risk that as a result of the failure of Doha round the path of multilateral trade liberalization will be fully replaced with the path of regionalism or, even worse, with the path of protectionism. The paper will examine the benefits of Doha round, the major restraints to complete negotiations and negative outcomes in case of failure. A special emphasis will be given to the analysis of the impact of the round on trade and economic development of CEE countries and especially on Lithuania
Ekonomia = Economics, 2011, Nr 2 (14), s. 32-39
Keywords: Doha; trade barriers; tariffs